Serum amyloid A and metabolic disease: evidence for a critical role in chronic inflammatory conditions - den Hartigh, Laura J.; May, Karolline S.; Zhang, Xue-Song; Chait, Alan; Blaser, Martin J. (Frontiers in Cardiovascular Medicine, 2023)
Serum amyloid A (SAA) subtypes 1–3 are well-described acute phase reactants that are elevated in acute inflammatory conditions such as infection, tissue injury, and trauma, while SAA4 is constitutively expressed. SAA subtypes also have been implicated as playing roles in chronic metabolic diseases including obesity, diabetes, and cardiovascular disease, and possibly in autoimmune diseases such as systemic lupus erythematosis, rheumatoid arthritis, and inflammatory bowel disease. Distinctions between the expression kinetics of SAA in acute inflammatory responses and chronic disease states suggest the potential for differentiating SAA functions. Although circulating SAA levels can rise up to 1,000-fold during an acute inflammatory event, elevations are more modest (∼5-fold) in chronic metabolic conditions. The majority of acute-phase SAA derives from the liver, while in chronic inflammatory conditions SAA also derives from adipose tissue, the intestine, and elsewhere. In this review, roles for SAA subtypes in chronic metabolic disease states are contrasted to current knowledge about acute phase SAA. Investigations show distinct differences between SAA expression and function in human and animal models of metabolic disease, as well as sexual dimorphism of SAA subtype responses.